Pharmacokinetics of levofloxacin in healthy Thai male volunteers - Suvatna Chulavatnatol (2018)
The pharmacokinetics of levofloxacin, a new fluoroquinolone, were investigated in 12 healthy Thai male volunteers with an average age (SD) of 22.92 (2.50) years. A single oral dose of 300 mg or 500 mg levofloxacin was given to subjects following an 8-hour overnight fast. The drug was given in a controlled, randomized, 2 x 2 crossover design with a 1 week washout period. Venous blood samples were drawn prior to and from 0.25 up to 48 hours after dosing. Plasma levofloxacin concentrations were determined by HPLC assay. The pharmacokinetics of levofloxacin were well described by a linear, 2-compartment open model with first-order absorption with lag time and first-order elimination. Mean ± SEM of Cmax after 300 mg and 500 mg dose was 4.83 ± 0.33 and 7.75 ± 0.71 μg/mL, respectively. Tmax ranged from 0.7 to 0.8 hours for both doses. Mean ± SEM of AUC0-∞ was 35.77 ± 2.06 μg x h/mL for 300 mg dose and 61.57 ± 2.84 μg x h/mL for 500 mg dose. High distribution with VSS/F value of approximately 1.5 L/kg was demonstrated after both doses. Mean ± SEM of CL/F value was 8.64 ± 0.41 L/h and 8.31 ± 0.37 L/h for a 300-mg and a 500-mg dose, respectively. Long t1/2ß of 7 to 8 hours with the mean residence time of 10.43 ± 0 43 hours and 10.49 ± 0.38 hours after 300 mg and 500 mg dose, respectively, was observed. The results suggested that an oral 300 mg dose once daily provides sufficient Cmax to cover most Gram-negative and atypical bacteria (median MIC90 0.032-0.5 μg/mL) common in mild to moderate respiratory tract infections or complicated urinary tract infections and Gram-positive bacteria (median MIC90 0.5 μg/mL) common in skin and soft tissue infections. For severe cases or Streptococcus pneumoniae (MIC90 2 μg/mL) infection, a 500-mg dose should be recommended.